Preface of the 4th International Conference on Future Technologies in Manufacturing, Automation, Design, and Energy 2024 (ICOFT 2024) - Karpagaraj Anbalagan; Murali Mohan Cheepu; M. V. A. Raju Bahubelendruni; Sendhil Kumar Natarajan (Engineering Proceedings)
This is the fourth in a series of conferences held annually in India, designed to disseminate knowledge on the latest technological developments and cutting-edge research in Manufacturing, Automation, Design, and Energy (MADE) among academicians, researchers, scientists, industry personnel, and entrepreneurs worldwide [...]